An integrated calcareous plankton biostratigraphic scheme and biochronology of the Mediterranean Middle Miocene - SPROVIERI, R.; BONOMO, S.; CARUSO, A.; DI STEFANO, A.; DI STEFANO, E.; FORESI, L. M.; IACCARINO, S.; LIRER, F.; MAZZEI, R.; SALVATORINI, G. (2002)
Based on the quantitative study of the calcareous nannofossils and planktonic foraminifera in three Mediterranean sections which cover the late Langhian - lower Tortonian stratigraphic interval, the relative position of 30 main bioevents belonging to the calcareous nannofossils and planktonic foraminifera have been identified in the time interval between 13.75 Ma and 10.50 Ma. They have been correlated, by a cyclostratigraphic approach, to the astronomic target curve. They thus allow for a very detailed biostratigrapbic and biochronologic subdivision of the interval. The zonal scheme proposed by Fornaciari et al. (1996) Is adopted for the calcareous nannofossils, but three subzones were identified in the MMN7 Zone. For the planktonic foraminifera, reference is made to the zonal scheme recently proposed by Foresi et al. (1998), but it is slightly modified in order to increase its biostratigraphic resolution. The age of all the zonal boundaries are reported.